Freshwater Mollusks of the World : A Distribution Atlas - Cummings, Kevin; Lydeard, Charles (Book collections on Project MUSE., 2019)
"Freshwater mollusks, invertebrates that protect themselves with a hard shell, fall into two major categories: gastropods--which have a single shell, such as snails--and bivalves--which have a double shell, such as clams and mussels. Mollusks are thought to be the second-largest group of animals behind arthropods, and while they live in almost every conceivable habitat from deep-sea vents to deserts, freshwater mollusks tend to be restricted to particular lake or river systems and are arguably the most endangered freshwater animal in the world. Despite their wide variety, little baseline data exists to help students and professionals understand mollusks' diversity and evolutionary relationships. Filling this gap in the literature could provide biogeographical insights, as mollusks' ancient fossil records go back over 500 million years and their distribution patterns are a reflection of past continental and climate changes. In this comprehensive reference book, world renowned experts tease apart the distributions of every freshwater mollusk family. The book provides basic biological and ecological information for each of the distinct 41 families, including summaries about the systematics and biodiversity of each family. Malacologists, limnologists, ichthyologists, stream ecologists, biogeographers, conservation biologists, and students will find this reference a must-have and one that will inform the study of mollusks for years to come"--